Dag Prawitz on Proofs and Meaning - Wansing, Heinrich (Springer, 2015)
The idea for the present volume goes back, as far as I remember, to a brainstorming among Ryszard Wójcicki, Jacek Malinowski, and myself at the Trends in Logic VII conference in Frankfurt/Main, September 2009. On the occasion of a meeting with a representative from Springer, Ryszard Wójcicki, quite enthusiastically, presented his thoughts on a new book series within the Studia Logica Library, an ambitious series meant to present Outstanding Contributions to Logic with volumes dedicated to eminent living logicians. It certainly comes as no surprise at all that during the brainstorming several important logicians immediately came to our minds and that Dag Prawitz was one of them...